Pré-Habilitação em pacientes com adenocarcinoma gástrico localmente avançado - Luís Carlos Paulos Cruz (2024)
Introduction: Stomach cancer has a high mortality rate worldwide, being the 3rd most deadly type of cancer in Portugal. The main incidence is in males and in the elderly. The prognosis is variable, depending on several individual factors. Both treatment and surgery affect people's physical fitness, reducing their overall quality of life. Physical activity plays a crucial role in prevention and in improving quality of life during treatment. The concept of prehabilitation aims to provide a strategy to optimize the physical, nutritional and mental fitness of patients before surgery, in order to improve the response to chemotherapy, reduce postoperative complications and decrease mortality rates. The report was developed within the scope of a curricular internship integrated into a clinical trial at IPO Porto. Objectives: To provide a comprehensive experience, both theoretical and practical, in the evaluation, monitoring and management of cancer patients together with the practice of physical exercise; to promote collaborative work in a multidisciplinary team, generating communication, empathy, organization and problem-solving skills. Methodology: PROTECT evaluates the efficacy of two physical exercise interventions, structured and unstructured, in reducing postoperative complications in patients with advanced gastric adenocarcinoma undergoing perioperative chemotherapy with FLOT regimen. Patients are physically assessed at three different time points. The exercise program begins before chemotherapy and continues until surgery, with weekly monitoring of symptoms, nutrition and adherence to exercise. Results: The physical fitness of participants PT125 and PTT140 (Protocol 1) showed an overall decline over time. PT133 (Protocol 2) maintained some physical fitness parameters but had a significant loss of muscle mass and strength, especially after surgery. Conclusion: Despite its limitations, the prehabilitation program showed benefits in maintaining physical fitness, especially in PT133, although it did not completely prevent postoperative physical decline.